PHARMACOGNOSTICAL AND PHYTOCHEMICAL EVALUATION OF LEAF OF ABUTILON INDICUM (LINN.) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Abutilon indicum (Linn) family (Malvaceae) commonly known as Atibala is used in our Traditional System of Medicine for healing various diseases. It is used in the treatment of piles, uterine discharge, febrifuge and in cases of pulmonary tuberculosis. In the present investigation an attempt was made to study its Pharmacognostical features, including macroscopic, microscopic features, physico-chemical parameters, leaf constants and to investigated the phytochemical present in the extracts in the preliminary level. Thus it was thought worthwhile to explore the plant on the basis of its standardization parameters. The study will provide a referential information for the correct identification of the crude drug.